2020
DOI: 10.1042/bsr20191449
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 gene rs6822844 polymorphism and rheumatoid arthritis susceptibility

Abstract: Interleukin-21 (IL-21) is a cytokine that plays a crucial role in pathogenesis and activity of the rheumatoid arthritis (RA). Meanwhile, genetic polymorphisms in the IL-21 gene may alter its expression. Previous studies have reported conflicting results assessing the association between the IL-21 rs6822844 G/T polymorphism and RA risk. Thus, it’s necessary to perform a meta-analysis to definite above relationship. PubMed database was searched for all papers published until October 20, 2019. Nine case–control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…The polymorphism found at rs1946518 of the IL18 gene is found in Egyptian populations, and the polymorphism found at rs549908 is found in the Taiwanese population. Thus the candidate genes for assessing genetic RA predisposition need to be thoroughly selected [ 19 , 20 , 21 , 22 ].…”
Section: Genetic Predisposition For Rheumatoid Arthritismentioning
confidence: 99%
“…The polymorphism found at rs1946518 of the IL18 gene is found in Egyptian populations, and the polymorphism found at rs549908 is found in the Taiwanese population. Thus the candidate genes for assessing genetic RA predisposition need to be thoroughly selected [ 19 , 20 , 21 , 22 ].…”
Section: Genetic Predisposition For Rheumatoid Arthritismentioning
confidence: 99%
“…Fibroblast-like synoviocytes (FLS) are an important type of synovial cell and are the main type of effector cell mediating joint destruction and synovitis by functioning in tissue shaping in the physiological state and in matrix remodeling in pathological injury (3)(4)(5)(6). At present, the specific pathogenesis of RA remains elusive, and may be related to immune factors, environmental factors, heredity, as well as other factors (7)(8)(9). Therefore, it is of great theoretical and practical significance to actively explore the pathogenesis of RA and search for potential diagnostic markers.…”
Section: Introductionmentioning
confidence: 99%
“…Reports including RA patients from different geographical regions showed the protective role of rs6822844 variant against RA development in the Netherlands [21], Algerian [22], Columbian [19] population. The latest meta-analysis further strengthens individual case-control observation [23].…”
Section: Discussionmentioning
confidence: 72%
“…Various reports have shown a signi cant association of IL-21 polymorphisms and RA in different populations such as Netherlanders [21], Algerian [22], Columbian [19]. Further, a recent meta-analysis with including nine various studies [23] demonstrated decreased susceptibility of IL-21 rs6822844 polymorphism against the development of RA. Although the association of IL-21 polymorphisms with RA has been studied in different populations, to date, it has not been explored in the Chinese community.…”
Section: Introductionmentioning
confidence: 99%